2018
DOI: 10.1371/journal.pone.0206118
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E, cognitive function, and cognitive decline among older Taiwanese adults

Abstract: Apolipoprotein E (APOE) genotype is believed to play a role in the onset of dementia, though less is known about its relationship with non-pathogenic age-related cognitive decline. We assessed whether APOE was a risk factor for cognitive decline among older Taiwanese adults using nationally representative data. General cognition was measured longitudinally over eleven years; domain-specific cognitive assessments of working memory, declarative learning and three aspects of attention (executive function, alertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
8
1
1
Order By: Relevance
“…26 The association between the ε4 variant and accelerated longitudinal cognitive decline has also been shown in community studies of both the Caucasian and Asian populations. 27,28 From the aspect of relative risk of dementia (i.e., AD and other dementia), it was not statistically significant depending on the presence of the APOE ε4 allele in present study. This finding was consistent with existing results community studies in the African, Hispanic, and Asian demographic.…”
Section: Discussioncontrasting
confidence: 67%
“…26 The association between the ε4 variant and accelerated longitudinal cognitive decline has also been shown in community studies of both the Caucasian and Asian populations. 27,28 From the aspect of relative risk of dementia (i.e., AD and other dementia), it was not statistically significant depending on the presence of the APOE ε4 allele in present study. This finding was consistent with existing results community studies in the African, Hispanic, and Asian demographic.…”
Section: Discussioncontrasting
confidence: 67%
“…Although the rate of cognitive decline and the risk of AD are not identical, the presence of complex gene-gene interactions of the APOE gene in both situations should be considered. A previous study using data from the Taiwan Longitudinal Study of Aging showed an association between the APOE genotype and the rate of cognitive decline in a predominantly Han Chinese population [ 3 ]. In the present study, the APOE gene ε4 allele was significantly associated with an earlier midpoint of cognitive decline in AD and MCI patients in both the Han Chinese population in Taiwan and ADNI population in America and associated with a rapid rate of cognitive decline in the Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, genetic background is one of the most important contributors to the rate of cognitive decline. The results from previous studies have shown that having at least one APOE ε4 allele was associated with faster cognitive decline in cognitively healthy older Taiwanese adults [ 3 ], and PDE7A and MTFR1 genes were associated with the rate of age-related cognitive decline [ 4 ]. Moreover, BDNF Val66Met was associated with faster cognitive decline and greater hippocampal atrophy in preclinical AD patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fungsi kognitif juga terkait dengan aktivitas mental yang dilakukan secara sadar seperti kemampuan berpikir, belajar dan penggunaan bahasa. 5 Dalam hasil penelitian yang dilakukan oleh Cinthya pada tahun 2019, diungkap bahwa sebanyak 75% dari 40 responden mengalami gangguan kognitif, dengan 57,5% responden mengalami gangguan kognitif ringan dan 17,5% mengalami gangguan kognitif sedang pada petani bunga akibat pajanan pestisida. 6 Penelitian lain juga telah dilakukan mengenai gangguan kognitif pada pekerja yang terpapar pestisida, hasilnya 39,1% petani jeruk yang menggunakan pestisida mengalami gangguan kognitif ringan.…”
Section: Pendahuluanunclassified